CAPITAL MARKET REACTION TO INVESTOR SENTIMENT ON SOCIAL MEDIA: SYSTEMATIC LITERATURE REVIEW - A. Anggi Reskiamalia; Muh Silmi Kaffa Yusuf; Syarifuddin; Darmawati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to systematically examine the relationship between investor sentiment on social media and capital market reactions in the context of modern finance. The approach used is Systematic Literature Review (SLR) with reference to the PRISMA guidelines, in order to identify, evaluate, and synthesize the results of previous research that are relevant and indexed in reputable journals. Analysis was carried out on publication trends, geographical context, sentiment analysis methods, and empirical results related to the influence of sentiment on stock prices, volatility, and other market variables. The results of the study show that investor sentiment on social media plays a significant role in influencing the dynamics of the capital market. Information spread through digital platforms such as Twitter, Reddit, and Weibo are able to shape the collective perception of investors which has a direct impact on stock price movements and volatility levels. These influences are heterogeneous, depending on the context of the country, type of industry, and economic conditions. Emerging markets and sectors with low levels of transparency tend to be more sensitive to changes in sentiment than more efficient developed markets. In addition, external factors such as economic crises, pandemics, and government policies strengthen the relationship between sentiment and market reactions. This research provides practical implications for investors in developing strategies based on sentiment analysis, for regulators in designing policies to supervise digital information, and for companies in strategically managing public communications. The next research recommendation is directed at the development of a quantitative model that integrates social media sentiment data with accounting and corporate governance variables to strengthen understanding of market behavior in the digital era.